Spectroscopy and microchip laser operation of Tm, Ho:KYW crystals with different Ho concentrations. (3rd January 2018) - Gusakova, N V; Kurilchik, S V; Yasukevich, A S; Kisel, V E; Dashkevich, V I; Orlovich, V A; Pavlyuk, A A; Vatnik, S M; Bagaev, S N; Kuleshov, N V
Abstract: The spectroscopic properties of Tm, Ho:KYW crystals with different Ho concentrations were investigated. The diode-pumped microchip laser operation of Tm (5 at.%), Ho (0.5 at.%):KYW and Tm (5 at.%), Ho (1 at.%):KYW was demonstrated. The highest, to our knowledge, output power of 480 mW with slope efficiency of 31% for CW Tm (5 at.%), Ho (0.5 at.%):KYW microchip laser was obtained.